2016
DOI: 10.1038/srep32950
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of type VI secretion system in secretion of iron chelator pyoverdine in Pseudomonas taiwanensis

Abstract: Rice bacterial blight caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most destructive rice diseases worldwide. Therefore, in addition to breeding disease-resistant rice cultivars, it is desirable to develop effective biocontrol agents against Xoo. Here, we report that a soil bacterium Pseudomonas taiwanensis displayed strong antagonistic activity against Xoo. Using matrix-assisted laser desorption/ionization imaging mass spectrometry, we identified an iron chelator, pyoverdine, secreted by P. taiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 44 publications
1
74
0
1
Order By: Relevance
“…Regulation of T6SS by Fur or iron has also been reported in E. coli , Edwardsiella tarda , Burkholderia mallei and Burkholderia pseudomallei s535455. Finally, a T6SS in Pseudomonas taiwanensis was recently shown to be involved in the secretion of the iron chelator pyoverdine by a yet unidentified mechanism56. Together, these observations suggest that iron uptake may be a common function of T6SSs.…”
Section: Discussionmentioning
confidence: 70%
“…Regulation of T6SS by Fur or iron has also been reported in E. coli , Edwardsiella tarda , Burkholderia mallei and Burkholderia pseudomallei s535455. Finally, a T6SS in Pseudomonas taiwanensis was recently shown to be involved in the secretion of the iron chelator pyoverdine by a yet unidentified mechanism56. Together, these observations suggest that iron uptake may be a common function of T6SSs.…”
Section: Discussionmentioning
confidence: 70%
“…PvdRT and OpmQ mediate the transport of the newly synthesized pyoverdine across the outer membrane and the recycling of pyoverdines. The FvpA receptor is a TonB-transporter family protein involved in pyoverdine-Fe sensing and internalization (Imperi et al, 2009; Cornelis, 2010; Schalk and Guillon, 2013; Gasser et al, 2015; Chen et al, 2016). fpvI that encodes for a RNA polymerase ECF-type sigma factor is also present in all the strains at the same locus.…”
Section: Resultsmentioning
confidence: 99%
“…Together with the report that T6SS is involved in Zn 2+ uptake in Y. pseudotuberculosis (32), our finding of the involvement of T6SS in Mn 2+ uptake significantly expands the range of known functions of this specialized protein secretion system. Recently, Chen et al (53) reported that the T6SS in Pseudomonas taiwanensis is involved in the secretion of iron chelator pyoverdine. Although the secretion mechanism of pyoverdine remains unidentified, this study implies the role of T6SS in iron uptake.…”
Section: Discussionmentioning
confidence: 99%